Selective hydroxyalkylation of phenol to bisphenol F over dodecatungstophosphoric acid (DTP) impregnated on fumed silica - Garade, Ajit C.; Kshirsagar, V. S.; Rode, C. V. (Applied Catalysis A-General, 2009)
The catalyst activity of various solid acids, such as fumed Silica (SiO(2)) dodecatungstophosphoric acid (DTP), DTP impregnated on SiO(2), amberlyst-15 and montmorillonite KSF/0, was studied for the hydroxyalkylation of phenol to bisphenol F. A well-dispersed DTP on SiO2 catalyst was prepared by the wet impregnation method. The effect of DTP loading on SiO(2) was also compared with bulk DTP and other solid acid catalysts. 20% DTP/SiO(2) catalyst gave the highest products yield of 34.2% and selectivity of 90.1% to bisphenol F, at 353 K and with a phenol-to-formaldehyde mole ratio of 5:1. Ammonia TPD studies of various catalysts showed that an appropriate combination of both strong and weak acid sites of DTP/SiO(2) Was mainly responsible, rather than only the stronger acidity of bulk DTP, for its highest catalytic activity and selectivity. The effect of various reaction parameters like mole ratio, catalyst concentration, temperature and reaction time on product yield and bisphenol F selectivity was also investigated. The catalyst recycle was established by catalyst activity testing. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Bisphenol F; Hydroxyalkylation; NH(3)-TPD; Reaction pathways; solid acid catalysts